2017
DOI: 10.1001/jamainternmed.2017.4836
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Thyroid Function With Life Expectancy With and Without Cardiovascular Disease

Abstract: IMPORTANCEVariations in thyroid function within reference ranges are associated with an increased risk of cardiovascular disease (CVD) and mortality. However, the impact of thyroid function on life expectancy (LE) and the number of years lived with and without CVD remains unknown.OBJECTIVE To investigate the association of thyroid function with total LE and LE with and without CVD among euthyroid individuals. DESIGN, SETTING, AND PARTICIPANTSThe Rotterdam Study, a population-based, prospective cohort study. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 46 publications
(95 reference statements)
6
55
1
Order By: Relevance
“…These data agree with the positive association between serum TSH levels and longevity reported in rodents [1][2][3] and euthyroid humans [3][4][5][6][7][8][9]. In line with these observations, rhTSH administration in human visceral adipocytes during 7 days, but not In parallel with these findings, a recent publication demonstrated that TSH administration (48h) in fully differentiated human adipocytes resulted in a significant improvement of mitochondrial biogenesis and function, increasing basal respiration, ATP production and spare respiratory capacity in parallel to increased SIRT1 and mitochondrial biogenesisrelated gene markers [22].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These data agree with the positive association between serum TSH levels and longevity reported in rodents [1][2][3] and euthyroid humans [3][4][5][6][7][8][9]. In line with these observations, rhTSH administration in human visceral adipocytes during 7 days, but not In parallel with these findings, a recent publication demonstrated that TSH administration (48h) in fully differentiated human adipocytes resulted in a significant improvement of mitochondrial biogenesis and function, increasing basal respiration, ATP production and spare respiratory capacity in parallel to increased SIRT1 and mitochondrial biogenesisrelated gene markers [22].…”
Section: Discussionsupporting
confidence: 91%
“…Euthyroid 50 year-old participants with increased levels of TSH had a longer life expectancy than participants with decreased serum TSH levels [4]. Increased TSH levels were also associated with lower mortality in participants between ages 85 and 90 [5] and in their offspring [6], and even in centenarians [7,8].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, it may often be recognized as one of the metabolic syndrome features. Also, TSH levels have been associated with increased body fat and BMI, as well as increased cardiovascular risk [35], although the studies are still controversial [36,37]. Within the reference range, it was already acknowledged that TSH levels seem to increase the BMI proportionally [38].…”
Section: Discussionmentioning
confidence: 99%